2019
DOI: 10.1128/mbio.01900-19
|View full text |Cite
|
Sign up to set email alerts
|

Panicum Mosaic Virus and Its Satellites Acquire RNA Modifications Associated with Host-Mediated Antiviral Degradation

Abstract: Positive-sense RNA viruses in the Tombusviridae family have genomes lacking a 5′ cap structure and prototypical 3′ polyadenylation sequence. Instead, these viruses utilize an extensive network of intramolecular RNA-RNA interactions to direct viral replication and gene expression. Here we demonstrate that the genomic RNAs of Panicum mosaic virus (PMV) and its satellites undergo sequence modifications at their 3′ ends upon infection of host cells. Changes to the viral and subviral genomes arise de novo within Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Previous studies showed that LDRIs can span significant distances within viral RNA genomes, ranging from one to several thousand nucleotides (Miller and White 2006;Nicholson and White 2014;Newburn and White 2015). Viral 3′ UTRs play an important role in viral replication and translation through LDRIs, and many of which belong to the Tombusviridae (Newburn and White 2015; Pyle et al 2019;Ilyas et al 2021). Efficient translation of PLPV of the genus Pelarspovirus relies on a TED-Like CITE in the 3′ UTR that communicates with the corresponding 5′-region through LDRI (Blanco-Pérez et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that LDRIs can span significant distances within viral RNA genomes, ranging from one to several thousand nucleotides (Miller and White 2006;Nicholson and White 2014;Newburn and White 2015). Viral 3′ UTRs play an important role in viral replication and translation through LDRIs, and many of which belong to the Tombusviridae (Newburn and White 2015; Pyle et al 2019;Ilyas et al 2021). Efficient translation of PLPV of the genus Pelarspovirus relies on a TED-Like CITE in the 3′ UTR that communicates with the corresponding 5′-region through LDRI (Blanco-Pérez et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, uridylation appears to be wide-spread in eukaryotic viruses. Although it is not fully clear, TUTases are more likely to attack viral RNA that lacks or with short A-tail, which may not be protected and is critical for host recognition of pathogens [ 92 , 95 , 96 , 97 ]. Consequently, uridylation promotes viral RNA degradation and protects host cells from viral invasion in some cases.…”
Section: U-rich Tail In Antiviral Innate Immune Responsementioning
confidence: 99%
“…The pool of polyadenylated RNA used for the above‐mentioned RNA‐seq study resulted in an intriguing follow‐up finding: alteration of PMV, SPMV and a satellite RNA (satRNA) during Brachypodium infection (Pyle et al , , ; Pyle & Scholthof, ). PMV is in the large virus family Tombusviridae , having single‐stranded RNA genomes defined, in part, by the lack of 7mG‐cap structures and 3′ ends that are not polyadenylated.…”
Section: Mechanisms Of Rna Modification Of the Host And Viruses Durinmentioning
confidence: 99%
“…Therefore, when we discovered that the viruses in the PMV complex had polyadenylated 3′‐ends it was a surprise. Upon further investigation, we identified and defined the polyadenylation of viral and subviral RNAs in natural infections of switchgrass ( Panicum virgatum ) and St. Augustinegrass ( Stenotaphrum secundatum ) and in laboratory infections of proso millet ( Panicum miliaceum ) and Brachypodium (Pyle et al , ). A host‐dependent viral recombination mechanism may control this, as the recombination sites of the satRNAs differed in Brachypodium and proso millet plants (Pyle et al , ; Pyle & Scholthof, ).…”
Section: Mechanisms Of Rna Modification Of the Host And Viruses Durinmentioning
confidence: 99%